Metaphor of Child Labor: Is it always negative? A Narrative Analysis - Agordzo Edoh-Torgah, Nyuiemedi (Universitas Ahmad Dahlan, 2018)
This paper explored how children caught up in child labor understand their experiences and positive outcomes. The qualitative narrative analytic approach was used to gather data through interviews with six participants: four students from two public Junior High Schools and two mothers. The study found that some child laborers find positive personal meaning in their suffering which promoted freedom, responsibility and improved school enrolment and educational achievement. Issues such as financial literacy, self-support and economic independence were found to be positive outcomes of their experiences. We concluded that positive personal meanings motivated child laborers to improve on their here-and-now and have hope for the future. We called for community counseling for parents and children to manage their time and funds appropriately and profitably; to help child laborers to have deeper meaning of their conditions and to have positive feelings and outlook on life.Â Keywords: child work, child labor, positivity, counseling, narrative analysis